DIGITAL LEADERSHIP: PARADIGM SHIFT AND ORGANIZATIONAL ADAPTATION CAPABILITIES - Yanita; Siti Nurhasanah; Zilla Syabrina Putri; Shintya Anggraini; Dwi Wulan Br Pardede; Alya Rahmi; Aulia Yunita Khairani (CV. Radja Publika, 2026)
The acceleration of Industry 4.0 demands a radical deconstruction of traditional, rigid and hierarchical leadership paradigms. This research aims to analyze the paradigm shift toward digital leadership and identify organizational adaptive capabilities for system transformation. The method used is a comparative literature review integrated with case study analysis of employee resistance to new technologies. The research results show that traditional leadership triggers bureaucratic stagnation and reduces functional efficiency. In contrast, digital leadership has been proven to increase operational efficiency through three main pillars: transparent horizontal communication governance, data -driven decision-making, and the creation of an agile work climate . Case analysis proves that cultural barriers in the form of internal resistance can be optimally resolved through digital leadership interventions combined with a situational approach. Leader flexibility in mapping the readiness level of followers, digital role models, and persuasive education are the main keys to reducing psychological conflict. Technology integration under the control of digital leadership has been proven to accelerate the system adoption curve to improve organizational performance sustainably.